Microbial, chemical, and isotopic monitoring integrated approach to assess potential leachate contamination of groundwater in a karstic aquifer (Apulia, Italy) - L. Beneduce; F. Piergiacomo; P. P. Limoni; L. E. Zuffianò; M. Polemio (Environmental Monitoring and Assessment, 2024)
Landfill sites are subjected to long-term risks of accidental spill of leachate through the soil and consequential contamination of the groundwater. Wide areas surrounding the landfill can seriously be threatened with possible consequences to human health and the environment. Given the potential impact of different coexisting anthropic pollution sources (i.e., agriculture and cattle farming) on the same site, the perturbation of the groundwater quality may be due to multiple factors. Therefore, it is a challenging issue to correctly establish the pollution source of an aquifer where the landfill is not isolated from other anthropic land uses, especially in the case of a karstic coastal aquifer. The present study is aimed at setting in place an integrated environmental monitoring system that included microbiological, chemical, and isotope methods to evaluate potential groundwater pollution in a landfill district in the south of Italy located in Murgia karstic aquifer. Conventional (microbial plate count and physical–chemical analyses) and advanced methods (PCR-ARISA, isotope analysis of δ 18 O, δ 2 H, 3 H, δ 13 C, δ 15 N-NO 3 − , and δ 18 O-NO 3 − ) were included in the study. Through data integration, it was possible to reconstruct a scenario in which agriculture and other human activities along with seawater intrusion in the karst aquifer were the main drivers of groundwater pollution at the monitored site. The microbiological, chemical, and isotope results confirmed the absence of leachate effects on groundwater quality, showing the decisive role of fertilizers as potential nitrate sources. The next goal will be to extend long-term integrated monitoring to other landfill districts, with different geological and hydrogeological characteristics and including different sources of pollution, to support the ecological restoration of landfills.

Coastal hydrogeological system of Mar Piccolo (Taranto, Italy) - L. E. Zuffianò; A. Basso; D. Casarano; V. Dragone; P. P. Limoni; A. Romanazzi; F. Santaloia; M. Polemio (Environmental Science and Pollution Research, 2016)